Analisis Pelaksanaan Proyek Pembangunan PLTU Suralaya Jawa 9&10 Cilegon Dengan Metode Earned Value Menggunakan Aplikasi MS Project 2019 - Jhon Jonathan Simanjuntak; Setiono Setiono; Fajar Sri Handayani (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2024)
This study aims to analyze the progress of the Suralaya Power Plant Project (Jawa 9&10 Cilegon) using the Earned Value Method (EVM) and MS Project 2019 application. The project's progress was tracked at weeks 15, 24, and 40 to identify the most optimal tracking point. The EVM metrics, including Earned Value (EV), Planned Value (PV), and Schedule Performance Index (SPI), were used to evaluate the project's performance. The results show that tracking the project at week 15 yielded the most optimal results compared to tracking at weeks 24 and 40. The SPI and CPI values at week 15 were closer to the target values, indicating better project performance. In contrast, the project's performance deteriorated at weeks 24 and 40, with SPI and CPI values deviating further from the target. The study concludes that tracking the project at week 15 is the most effective method for monitoring project progress, as it allows for early identification of potential issues and timely corrective actions. This research contributes to the body of knowledge on project management in the energy sector, highlighting the importance of regular tracking and monitoring in ensuring the successful implementation of large-scale infrastructure projects.